(untitled) (Symposium on Natural and Applied Sciences, 2026)
This article examines the organizational and legal foundations for the development of ethnocultural tourism (ethnotourism) in Uzbekistan. The study analyzes the existing national legal framework and compares it with international practices to identify key institutional and regulatory gaps. Using comparative, systemic, and analytical methods, the research evaluates the effectiveness of tourism governance mechanisms and legal instruments. The findings indicate that Uzbekistan’s tourism legislation remains generalized and lacks specific provisions for ethnotourism development, which limits the efficient utilization of ethnocultural resources. Comparative analysis with countries such as Spain and Japan demonstrates that specialized legal frameworks and strong community participation significantly enhance tourism performance. The paper proposes evidence-based recommendations, including the adoption of a dedicated law on ethnotourism, strengthening local governance, and introducing financial incentives. The results contribute to the theoretical and practical understanding of tourism policy and provide a basis for improving the legal environment for sustainable ethnotourism development in Uzbekistan.